A música na sala de aula: a sua importância para o desenvolvimento de crianças dos anos iniciais do Ensino Fundamental - Almeida, Giovanna Gomes da Silva (Brasil, 2025)
Music plays a fundamental role in child development, especially in the early years of elementary school, contributing to motor, cognitive, emotional and social skills. In the school context, it stands out as a pedagogical tool that makes the classroom environment more dynamic, interactive and enjoyable, highlighting the importance of its inclusion in educational planning. Musical activities promote motor development through fine and gross motor coordination, in addition to stimulating cognitive development, requiring concentration, memorization and organization of thought. These aspects favor performance in areas such as language, mathematics and creativity, positioning music as an interdisciplinary resource with high potential. Musicality also develops skills such as aesthetic sensitivity, auditory perception, emotional expression and social interaction. Singing, playing instruments or participating in musical dynamics enable forms of communication beyond verbal language, promoting collaboration, mutual respect and the healthy expression of feelings. These practices strengthen self-esteem, empathy and creativity, essential skills for problem-solving. However, a critical analysis reveals that school environments often do not encourage children's engagement, resulting in difficulties in the teaching-learning process, as students are unable to associate meaning with the knowledge acquired in the classroom. In addition to enhancing learning, music also promotes students' emotional and psychological well-being. It transforms the act of learning into a meaningful experience, creating emotional bonds between peers and teachers, and contributing to a welcoming and motivating educational environment. Thus, integrating music into the school context goes beyond the development of academic skills, providing global benefits for child development.